1992
DOI: 10.1021/ma00031a007
|View full text |Cite
|
Sign up to set email alerts
|

Living metathesis polymerization of [o-(trifluoromethyl)phenyl]acetylene by molybdenum-based three-component catalysts

Abstract: Living metathesis polymerization of [o- (trifluoromethyl)phenyl] acetylene, a phenylacetylene with an electron-withdrawing group, has been achieved by using molybdenum-based three-component catalysts. Thus polymerization by MoOCWt-BuiSn-EtOH (1:1:0.5 mole ratio) catalyst in toluene at 30 °C produced a polymer having a narrow molecular weight distribution; MjMa = 1.06. Upon three consecutive additions of fresh monomer feeds to completely polymerized systems, the M" of the polymer increased in direct proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…50 Thus the polymerization by MoOCl 4 -n-Bu 4 Sn-EtOH (1:1:0.5 mol ratio) catalyst in toluene at 30 8C produced a polymer with narrow MWD; M w /M n ¼ 1.06. Upon three consecutive additions of fresh monomer feeds to completely polymerized systems, the M n of the polymer increased in direct proportion to monomer conversion, while the M w /M n remained <1.1.…”
Section: Metathesis Mechanismmentioning
confidence: 97%
“…50 Thus the polymerization by MoOCl 4 -n-Bu 4 Sn-EtOH (1:1:0.5 mol ratio) catalyst in toluene at 30 8C produced a polymer with narrow MWD; M w /M n ¼ 1.06. Upon three consecutive additions of fresh monomer feeds to completely polymerized systems, the M n of the polymer increased in direct proportion to monomer conversion, while the M w /M n remained <1.1.…”
Section: Metathesis Mechanismmentioning
confidence: 97%
“…Detailed polymerization procedures were described before. 5 Monomer conversions were determined by measuring the initial and final monomer concentrations by GC (silicone DC 3 m, 170°C). The MWD curves of polymers were observed by gel permeation chromatography (GPC) using a Jasco Trirotar liquid chromatograph (Shodex A803, A804, and A805 polystyrene gel columns, eluent CHC1 3 ), and the number-and weight-average molecular weights (.M.…”
Section: Experiments Almentioning
confidence: 99%
“…The authors have found that molybdenum-based three-component catalysts, i.e., MoOClc(or MoC1 5 )-n-Bu4 SnEtOH effect living polymerization of substituted acetylenes such as l -chloro-l -octyne 3 · 4 and [o-(trifluoromethyl)phenyl]acetylene. 5 Silicon-containing polyacetylenes are characterized by unique properties like high gas permeability. 6 Examples of such polymers with high molecular weight include poly[l-(trimethylsilyl)-1-propyne] and poly [[o-(trimethylsilyl) In the present note, we report on the living polymerization of o-Me 3 SiPA effected * To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…Polymerization of substituted acetylenes by group 5 and 6 transition metal catalysts is believed to proceed via metal carbenes as active species and metallacyclobutenes as intermediates (Scheme 1) 3,4) . Recently, precise synthesis of polymers aroused much attention, and living polymerization of substituted acetylenes is making remarkable progress as well as those in other polymerization processes [4][5][6][7][8][9] . We have found that the MoOCl 4 -n-Bu 4 Sn -EtOH (1 : 1 : 1)/toluene catalyst induces living polymerization of various substituted acetylenes [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, precise synthesis of polymers aroused much attention, and living polymerization of substituted acetylenes is making remarkable progress as well as those in other polymerization processes [4][5][6][7][8][9] . We have found that the MoOCl 4 -n-Bu 4 Sn -EtOH (1 : 1 : 1)/toluene catalyst induces living polymerization of various substituted acetylenes [7][8][9] . It is considered that n-Bu 4 Sn reacts with MoOCl 4 as alkylating agent to produce a metal carbene in this catalyst system.…”
Section: Introductionmentioning
confidence: 99%